A Local Problem Preventing Cardiopulmonary Bypass (Annals of Medical Research, 2021)
None
Keywords: Cardiopulmonary Bypass, Taenia Saginata, İmmun Deficiency, Coronary Artery Bypass Grafting Surgery, Open Heart Surgery